2016
DOI: 10.5130/lns.v24i2.4809
|View full text |Cite
|
Sign up to set email alerts
|

Adult reading teachers’ beliefs about how less-skilled adult readers can be taught to read.

Abstract: Despite large-scale interventions, significant numbers of adults worldwide continue to have problems with basic literacy, in particular in the area of reading. To be effective, adult reading teachers need expert knowledge at practitioner level. However, practices in adult reading education vary widely, often reflecting the individual beliefs of each teacher about how an adult can learn to read. In this study, phenomenographic analysis was used to identify categories of approaches to teaching adult reading, use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Encouraging autonomy is closely related to building learners' self-efficacy, or their belief in their own ability to gain new knowledge. Self-efficacy is an essential contributor to learner motivation (Crevecoeur 2011;McHardy and Chapman 2016;Norton and Toohey 2011;Po-ying 2007) and learning (Dornyei 1994;Seaton 2018). ABE learners have 'lower levels of perceived self-efficacy' (Rothes et al 2017:8) and, due to their limited education, ALL often display this trait as well (Centre for Canadian Language Benchmarks 2016).…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraging autonomy is closely related to building learners' self-efficacy, or their belief in their own ability to gain new knowledge. Self-efficacy is an essential contributor to learner motivation (Crevecoeur 2011;McHardy and Chapman 2016;Norton and Toohey 2011;Po-ying 2007) and learning (Dornyei 1994;Seaton 2018). ABE learners have 'lower levels of perceived self-efficacy' (Rothes et al 2017:8) and, due to their limited education, ALL often display this trait as well (Centre for Canadian Language Benchmarks 2016).…”
Section: Self-efficacymentioning
confidence: 99%
“…Those enrolled may also receive social assistance. LINC teachers are struggling under the influx of low-literate refugees from the Middle East and East Africa in particular, due to inadequate training in adult literacy learner instruction (Ewert 2014, McHardy andChapman 2016). In some contexts, it has been found that even when training is provided, teachers are not always implementing the training they have received (Crevecoeur 2011;Gerner 2018), and often resort to teaching as they were taught (DeCapua, Marshall and Frydland 2018;Ewert 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In one previous study conducted by the authors, 60 adult reading teachers were asked to discuss their beliefs about how less-skilled adult readers should be taught to read (McHardy & Chapman, 2016). In this phenomenographic study, the adult reading teachers responded to an online survey on the instructional approaches they would use to teach a specific, profiled adult reader.…”
mentioning
confidence: 99%
“…Given the research evidence which suggests that adult reading teachers often rely upon their own beliefs about the reading process in deciding upon their instructional strategies, rather than on evidence garnered from well-controlled research within the field (McHardy & Chapman, 2016;Benseman, 2013;Van Kan et al, 2013), to change teachers' practices and facilitate the adoption of responsive approaches in adult reading programs, it will first be necessary to extend our own understanding of the perspectives adopted by reading teachers (Barnyak & Paquette, 2010). There is limited reference to the origins of reading-related beliefs and perspectives in the adult teacher education literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation